Recurrent Postoperative Spinal Epidural Hematoma in a Patient with Protein S Deficiency. (7th July 2015) - Anno, Masato; Yamazaki, Takashi; Hara, Nobuhiro; Hayakawa, Keishi
Abstract : A 71-year-old man underwent cervical laminectomy and developed two symptomatic epidural hematomas during the acute postoperative period. On both occasions, drain obstruction was the predominant cause. Congenital Protein S deficiency was diagnosed postoperatively. Protein S is a vitamin K-dependent natural anticoagulant and is essential for inhibiting thrombosis in microcirculation. We assume that Protein S deficiency followed by perioperative bed-rest and surgical invasiveness led to severe hypercoagulability and subsequent drain obstruction. The present findings suggest that both bleeding disorders and hypercoagulability are risk factors for postoperative symptomatic epidural hematoma.